370 Pharmacodynamic assessment of a novel FAP-targeted 4–1BB agonist, administered as single agent and in combination with atezolizumab to patients with advanced solid tumors. (9th November 2020) - Moreno, Victor; Hernandez, Tatiana; Melero, Ignacio; Sanmamed, Miguel; Spanggaard, Iben; Rohrberg, Kristoffer Staal; Tabernero, Josep; Azaro, Analia; Garcia, Maria Martinez; Rodriguez-Vida, Alejo; Claus, Christina; Heil, Florian; et al.
Abstract : Background: RO7122290 (RO) is a bispecific antibody-like fusion protein that simultaneously targets FAP, abundantly expressed by cancer-associated fibroblasts in most solid tumors, and 4-1BB, transiently expressed on activated T cells. Pre-clinical experiments revealed strong intra-tumoral CD8+ T cells infiltration in FAP-positive tumors, cytokines induction and significant anti-tumor activity mediated by RO (signal 2 of T cell activation), upon TCR/CD3 engagement (signal 1) or in combination with atezolizumab (ATZ). In this first-in-human study, the pharmacodynamic (PD) effects of RO were assessed, both as single agent (SA) (Part A) and in combination with ATZ (Part B). Methods: Pts with advanced and/or metastatic solid tumors were eligible for this ongoing Phase 1/1b trial (EUDRACT 2017-003961-83). RO was administered intravenously, weekly (QW) at escalating dose levels (DLs). In Part A, 62 pts were treated at 13 DLs of RO, dose range 5–2000 mg. In Part B, 39 pts were treated at 8 DLs of RO, dose range 45–2000 mg, with ATZ 1200 mg Q3W. Secondary biomarker objective was characterization of PD effects in tumor tissue and blood. The endpoints were change from baseline in intra-tumoral density (cell/mm 2 ) and proliferation (Ki67) of CD8+ T cells measured by immunohistochemistry (IHC), and change in activation (4-1BB) and proliferation (Ki67) of peripheral CD8+ T cells measured by flow cytometry. Exploratory objectives were characterization of PD effects in plasma/serum and measurement of intra-tumoral immune activation. The endpoints were change in peripheral cytokines (TNF-alfa, IFN-gamma, IL-6) and soluble(s) factors (sCD25, s4-1BB) concentration measured by ELISA, and intra-tumoral changes in gene expression measured by RNAseq. Results: In the periphery, we observed transient expression of 4-1BB on CD4+ and CD8+ T cells, along with secretion of s4-1BB and inflammatory cytokines, suggesting 4-1BB targeting and potent T cell activation. The concomitant induction of proliferating T cells indicated the potential association to priming and formation of tumor-reactive T cells. In the tumor, we detected increased CD8+ T cells infiltration and proliferation, in both Parts. Proliferating CD8+ T cells increased in both tumor nests and surrounding stroma, with a preferential accumulation in the latter. RNAseq analysis revealed induction of 4-1BB, PD-1 and IFN-gamma, indicating intra-tumoral T cells activation in Part B. Conclusions: PD activity was consistent with the postulated MoA, confirming RO to be a potent tumor-targeted 4-1BB agonist in the clinical setting. Our observations suggest that RO can synergize with endogenous T cell receptor stimulation, both as SA and in combination with ATZ.